2016
DOI: 10.1177/0194599815617752
|View full text |Cite
|
Sign up to set email alerts
|

Ménière’s Disease

Abstract: Objective 1) Integrate practice-based patient encounters using the Dartmouth Atlas Medicare database to understand practice treatments for Meniere's Disease (MD). 2) Describe differences in the practice patterns between academic and community providers for MD. Study Design Practice-based research database review. Setting “CHEER Network” academic and community providers. Subjects and Methods MD patient data were identified using ICD-9 and CPT codes. Demographics, unique visits, and procedures per patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…This plateau in intratympanic injection usage is a novel finding and may represent general acceptance of the strategy in tertiary centers comprising the cohort. Academic practices were previously observed to utilize such procedural treatment more frequently for MD than community centers 4,9 . Analysis of treatment trends in community practices after guideline publication might reveal trends not observed here.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This plateau in intratympanic injection usage is a novel finding and may represent general acceptance of the strategy in tertiary centers comprising the cohort. Academic practices were previously observed to utilize such procedural treatment more frequently for MD than community centers 4,9 . Analysis of treatment trends in community practices after guideline publication might reveal trends not observed here.…”
Section: Discussionmentioning
confidence: 56%
“…Academic practices were previously observed to utilize such procedural treatment more frequently for MD than community centers. 4,9 Analysis of treatment trends in community practices after guideline publication might reveal trends not observed here.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, once a patient receives a definite diagnosis of MD, there is no universally accepted standard of care. Crowson et al (33) demonstrated that academic otolaryngologists perform significantly more operative procedures for MD patients than community otolaryngologists, although these variations have multiple explanations including operating room variability, training and ability, along with operative case referral.…”
Section: Discussionmentioning
confidence: 99%
“…Die Neuropathia vestibularis (NV) ist nach dem benignen paroxysmalen Lagerungsschwindel (BPLS) die zweithäufigste Ursache für peripher-vestibulären Schwindel [1]. Im Vergleich zu periphervestibulären Schwindelerkrankungen wie dem Morbus Menière oder dem BPLS gibt es für die NV nur unzureichend Daten aus großen demografischen Studien [2,3].…”
Section: Introductionunclassified